THE INFLUENCE OF LEADERSHIP STYLE, CAREER DEVELOPMENT AND INDIVIDUAL COMMITMENT ON EMPLOYEE PERFORMANCE AT ALFAMART IN BATAM CITY - Wasiman Wasiman; Yvonne Wangdra; Suhardi Suhardi; Syaifullah Syaifullah (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
The research implementation was based on a research on research objects, namely Alfamart in Batam City with limited problems at Alfamart in the Sekupang area. This study aims to analyze and determine the influence of leadership style, career development and individual commitment to employee performance at Alfamart in Batam City. In carrying out this research using the method of distributing questionnaires to Alfamart employees in Batam City, with a total sample of 120 samples used in this study. Several tests were used, such as respondent's test, validity test, reliability test, normality test, t test, r test and f test. Based on the results of the validity test, it can be concluded that all the data used is valid and can be continued for reliability tests and other follow-up tests. Based on the results of the t test, it was found that the leadership style variable had a positive and significant effect on employee performance at Alfamart in Batam City. Furthermore, career development variables and individual commitment have a significant effect on employee performance at Alfamart in Batam City. The results of the Adjusted R-Square test show that performance variables can be influenced by leadership style, career development and individual commitment variables by 84%. The results of the f test conclude that all variables have a significant effect on employee performance at Alfamart in Batam City.